2008
DOI: 10.1007/s10815-008-9208-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone and in vitro maturation of rhesus macaque oocytes and subsequent embryo development

Abstract: The presence of GH receptors along with increased cumulus expansion and embryos progressing to the 9-16 cell stage supports the hypothesis that r-hGH may be involved in oocyte maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 66 publications
5
37
0
Order By: Relevance
“…Previous studies using the rhesus model have noted that oocyte quality is improved with in vivo exposure to the maturing follicle [10,12,27,29]. This study is consistent with previous studies in which changes in gene expression within all follicular cell types were reported during the last 24 h of VVM with hCG [27,29], and with studies showing changes in oocyte gene expression related to cell-cell communication [27].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies using the rhesus model have noted that oocyte quality is improved with in vivo exposure to the maturing follicle [10,12,27,29]. This study is consistent with previous studies in which changes in gene expression within all follicular cell types were reported during the last 24 h of VVM with hCG [27,29], and with studies showing changes in oocyte gene expression related to cell-cell communication [27].…”
Section: Discussionsupporting
confidence: 91%
“…Adult female rhesus macaques (Macaca mulatta) were housed at the California National Primate Research Center, as previously described [10].…”
Section: Animal Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…Adult female rhesus macaques (Macaca mulatta) were housed at the California National Primate Research Center (CNPRC) as described previously (47). Only females with a history of normal menstrual cycles were selected for this study.…”
Section: Methodsmentioning
confidence: 99%